Role of echocardiography in the assessment of right ventricular function in the pediatric population. Issue 5 (2nd May 2019) - Kamra, Komal; Punn, Rajesh
Abstract: This review article summarizes the use of echocardiography in the evaluation of the right ventricle with special emphasis on pediatric patients. After reading this article, anesthesiologists will develop a better understanding of the anatomy and echocardiographic parameters for hemodynamic and functional assessment of the right ventricle. This knowledge will assist with the perioperative management of patients with cardiopulmonary disorder.